THE RISE AND GROWTH OF CHALLENGER BANKS IN THE UK: A profitability and efficiency study - Bennison, Matthew (2022)
This study examines the determinants of profitability for a selection of UK banks and building societies and analyses their efficiency over the period 2014-2020. A single-step Stochastic Frontier Analysis is used for cost efficiency analysis, and profitability is analysed through a series of OLS, fixed effects and random effects models for a panel data set to analyse the key determinants of UK bank profitability. The results demonstrate that challenger banks are less cost efficient and that their cost efficiency is more volatile than larger banks, particularly during times of hardship or uncertainty like the pandemic. The results from the regressions indicate that the largest banks experience higher profitability and efficiency, since size is statistically significant and positively related to profitability, but evidence of diminishing returns to scale are found to a point where the largest firms experience a negative relationship between increasing size and profitability. Challenger banks experience a positive relationship with cost-to-income but a negative relationship with equity-to-assets, whereas the largest firms see the opposite results.